Chemokine (C‐X‐C motif) ligand 11 levels predict survival in cirrhotic patients with transjugular intrahepatic portosystemic shunt. (17th August 2015) - Berres, Marie‐Luise; Lehmann, Jennifer; Jansen, Christian; Görtzen, Jan; Meyer, Carsten; Thomas, Daniel; Zimmermann, Henning W.; Kroy, Daniela; Schumacher, Fabienne; Strassburg, Christian P.; Sauerbruch, Tilman; Trautwein, Christian; et al.
Abstract: Background & Aims: Chemokines, such as CXCR3‐ligands, have been identified to play an important role during hepatic injury, inflammation and fibrosis. While CXCL9 is associated with survival in patients receiving transjugular intrahepatic portosystemic shunt (TIPS), the role of CXCL11 in severe portal hypertension remains unknown. Methods: CXCL11‐levels were measured in 136 patients with liver diseases, and 63 healthy controls. In further 47 cirrhotic patients receiving TIPS, CXCL11 levels were measured in portal and hepatic veins at TIPS insertion by cytometric bead array. CXCL11‐levels were measured in 23 patients in cubital vein and right atrium, whereas in 24 patients in portal and hepatic blood at an invasive reevaluation. Results: CXCL11‐levels were increased with the severity of liver fibrosis. CXCL11‐levels from portal, hepatic and cubital veins and right atrium showed a highly significant correlation among each other in these patients. Furthermore, levels of CXCL11 from the right atrium were significantly higher than those from cubital vein. Interestingly, patients with alcoholic cirrhosis had significantly lower CXCL11‐levels, than other aetiologies of cirrhosis. After TIPS, CXCL11 levels correlated with the degree of portal pressure and patients with higher CXCL11‐levels in portal and hepatic veins showed higher mortality. Multivariate analysis revealed hepatic CXCL11‐levels before TIPS, creatinine and age as independent predictors for survival in TIPS patients, whereas MELD score and low portal CXCL11‐levels after TIPS predicted long‐term survival. Conclusion: CXCL11 levels are mainly increased in patients with non‐alcoholic cirrhosis and high portal pressure. Moreover, levels of CXCL11 might predict long‐time survival of cirrhotic patients bearing TIPS.